Haemorrhagic pericardial effusion as the presenting symptom of scurvy - Joulal, Hajar; Yousfi, Jaouad; Benjilali, Laïla; Zahlane, Mouna; Essaadouni, Lamiaa (European Journal of Case Reports in Internal Medicine, 2023)
Introduction: Vitamin C deficiency (or scurvy) usually takes weeks to become apparent as cutaneous signs and impaired wound healing. Haemorrhagic pericarditis remains a rare complication of scurvy, which has never been reported as an isolated condition. We report the case of a haemorrhagic pericarditis revealing a vitamin C deficiency in a 56-year-old patient. Case description: A 56-year-old woman presented with a 2-week history of worsening chest pain and dyspnoea, with no significant medical history. Upon admission, the patient exhibited tachycardia, tachypnoea, low blood pressure, elevated jugular venous pressure, muffled heart sounds and multiple petechiae on her lower limbs. An ultrasound revealed a large pericardial effusion, and an emergency pericardiocentesis was performed, which yielded haemorrhagic fluid without atypical cells. An initial workup including haemoculture, PT and PTT, tuberculosis workup, autoantibodies, tumour markers and infectious disease was negative. A whole-body CT scan showed no evidence of tuberculosis or lymphoma. Additional testing showed that her vitamin C level was <3 umol/L. Following stabilisation, high-dose vitamin C therapy was initiated. Subsequently, she showed continued clinical improvement and remained asymptomatic upon her discharge. Discussion: While uncommon, it is crucial to investigate vitamin C deficiency when confronted with an unexplained haemorrhagic pericardial effusion, particularly in patients with risk factors. Conclusion: Our case highlights the significance of early detection of this condition in promptly addressing the diverse complications of scurvy, thereby enhancing the prognosis of a potentially fatal condition.